2017
DOI: 10.4103/jisppd.jisppd_257_16
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of two different behavioral modification techniques among 5–7-year-old children: A randomized controlled trial

Abstract: TPD is effective in reducing children's fear and anxiety about dental treatment, children enjoy playing with customized dental object. Thus, to promote adaptive behavior, TPD could be an alternate behavioral modification technique during pediatric dentistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 1 publication
5
41
0
6
Order By: Relevance
“…Hence, this justifies being the method of choice for patient education and behavior guidance during the first dental visit. 6 Previous studies have also shown distraction to be a helpful intervention for individuals undergoing stressful procedures. For example, patients undergoing dental procedures with distraction report less anxiety, discomfort, and distress.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, this justifies being the method of choice for patient education and behavior guidance during the first dental visit. 6 Previous studies have also shown distraction to be a helpful intervention for individuals undergoing stressful procedures. For example, patients undergoing dental procedures with distraction report less anxiety, discomfort, and distress.…”
Section: Discussionmentioning
confidence: 99%
“…5 The first dental experience is important in molding child's attitude toward dentistry and dental outcome. 6 It is essential to identify anxious children at the earliest age possible in order to institute a precocious behavioral treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly according to Vishwakarma et al, sight, sound, and sensation of the airotor are to be rated as the most fear-eliciting stimuli. 10 Response to feared stimulus is multifaceted and has cognitive, physiological, and behavioral dimensions. 11 The physiological impact involves activation of the autonomic nervous system (i.e., increased heart rate, blood pressure, and skin conductance) and the limbic-hypothalamic-pituitary-adrenal axis (i.e., release of the stress hormone, cortisol).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have found the TPD method to be more effective in reducing dental anxiety, when compared with the modelling method. Furthermore, the paediatric patients (the examined group were individuals aged 5-7) have proven more eager to cooperate with every subsequent visit to the dentist [9]. In the case of adults, practitioners can modify the method to make it more effective and suitable for the patient's needs.…”
Section: Basic Behavioural Methodsmentioning
confidence: 99%